Optimizing Energy and Electricity Manage-ment Through Technical and Economic Analysis of Automation Technology Lifecy-cle Management in Power Plants - Wanto, Weldi (Publikasi Indonesia, 2025)
The rapid advancement of automation technology in power plants has created a need for com-prehensive lifecycle management analysis to ensure that technical and economic aspects are op-timized throughout the plant's operation. This study focuses on improving energy and electricity management by evaluating the lifecycle stages of automation technology, including a case study on a specific product. The technical analysis examines the compatibility of new automation technology with existing infrastructure and its scalability for future upgrades, while the econom-ic analysis considers initial capital investment, operational costs, and long-term savings from in-creased efficiency and reduced downtime. By integrating both technical and economic perspec-tives, this study offers a holistic approach to enhancing energy and electricity management. Ef-fective lifecycle management of automation technology in power plants is essential for improv-ing operational efficiency, ensuring cost-effectiveness, and supporting sustainable energy man-agement. This research contributes to a deeper understanding of the relationship between tech-nical performance and economic considerations, advancing the field of power plant automation technology and optimizing the management of automation systems throughout their lifecycle